Insights into an Optimization of Plasmodium vivax Sal-1 In Vitro Culture: The Aotus Primate Model. - Kathryn Shaw-Saliba; Richard Thomson-Luque; Nicanor Obaldía; Marlon Nuñez; Sahir Dutary; Caeul Lim; Samantha Barnes; Clemens H M Kocken; Manoj T Duraisingh; John H Adams; Erica M Pasini (Public Library of Science (PLoS), 2016)
Malaria is one of the most significant tropical diseases, and of the Plasmodium species that cause human malaria, P. vivax is the most geographically widespread. However, P. vivax remains a relatively neglected human parasite since research is typically limited to laboratories with direct access to parasite isolates from endemic field settings or from non-human primate models. This restricted research capacity is in large part due to the lack of a continuous P. vivax in vitro culture system, which has hampered the ability for experimental research needed to gain biological knowledge and develop new therapies. Consequently, efforts to establish a long-term P. vivax culture system are confounded by our poor knowledge of the preferred host cell and essential nutrients needed for in vitro propagation. Reliance on very heterogeneous P. vivax field isolates makes it difficult to benchmark parasite characteristics and further complicates development of a robust and reliable culture method. In an effort to eliminate parasite variability as a complication, we used a well-defined Aotus-adapted P. vivax Sal-1 strain to empirically evaluate different short-term in vitro culture conditions and compare them with previous reported attempts at P. vivax in vitro culture Most importantly, we suggest that reticulocyte enrichment methods affect invasion efficiency and we identify stabilized forms of nutrients that appear beneficial for parasite growth, indicating that P. vivax may be extremely sensitive to waste products. Leuko-depletion methods did not significantly affect parasite development. Formatting changes such as shaking and static cultures did not seem to have a major impact while; in contrast, the starting haematocrit affected both parasite invasion and growth. These results support the continued use of Aotus-adapted Sal-1 for development of P. vivax laboratory methods; however, further experiments are needed to optimize culture conditions to support long-term parasite development.